2007
DOI: 10.1038/sj.onc.1210699
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polyomaviruses and herpesviruses in human adrenal tumors

Abstract: The presence of polyomaviruses and herpesviruses in adrenal tumors and their role in adrenal tumorigenesis has never been investigated, even though the adrenal gland seems to be a preferential site of infection by these viruses and adrenal steroid hormones have been shown to activate their replication. We examined in a large series of normal adrenal gland tissues (n ¼ 20) and adrenal tumors (n ¼ 107) the presence of herpesviruses and polyomaviruses sequences and gene expression, which were detected in a high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The pathogenesis is unknown, but detection of Epstein Barr virus (EBV) genome sequences and gene expression in 9 out of 20 cases of primary adrenal lymphomas suggested the virus might be the causative agent of the malignancy [ 6 ]. While investigating the presence of genome sequences of oncogenic viruses in a large series of adrenal tumors and their potential association with malignancy [ 7 ], both EBV and JC polyomavirus (JCV) DNA sequences were detected in the case of primary bilateral adrenal B-cell lymphoma we are reporting here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis is unknown, but detection of Epstein Barr virus (EBV) genome sequences and gene expression in 9 out of 20 cases of primary adrenal lymphomas suggested the virus might be the causative agent of the malignancy [ 6 ]. While investigating the presence of genome sequences of oncogenic viruses in a large series of adrenal tumors and their potential association with malignancy [ 7 ], both EBV and JC polyomavirus (JCV) DNA sequences were detected in the case of primary bilateral adrenal B-cell lymphoma we are reporting here.…”
Section: Resultsmentioning
confidence: 99%
“…A diagnosis of diffuse large B-cell non-Hodgkin lymphoma was made. To investigate whether oncogenic viruses were involved in the disease, both left and right adrenal masses were examined for the presence of all human herpesviruses and polyomaviruses by quantitative real-time PCR, as reported [ 7 ]. EBV DNA was present at high titre (about 100 genome copies/cell) and JCV DNA at lower titre (about 0.1 genome copy/cell) in both adrenal masses.…”
Section: Resultsmentioning
confidence: 99%
“…Another study examined adrenal glands and adrenal tumors for the presence of viral sequences, since the adrenal gland is located on top of the kidney, a major site of BKV persistence. This study found 4 out of 107 adrenal tumor samples positive for BKV by both real-time PCR and IHC for TAg [130]. Normal tissue samples were all negative, suggesting that BKV may be associated with adrenal tumors, possibly due to the proximity of the adrenal gland to the kidney and its ability to produce hormones known to stimulate BKV gene expression [131].…”
Section: Bk Virus and Human Tumorsmentioning
confidence: 99%
“…In spite of these numerous studies, the mechanistic role of BKV in human malignancies remains highly debatable. BKV DNA and proteins have been found in renal, bladder, prostate, pancreatic, adrenal, and brain cancer tissues (Corallini et al, 1987;Flaegstad et al, 1999;Fioriti et al, 2005;Barzon et al, 2008;Taghavi et al, 2015;Yin et al, 2015). On the other hand, several reports have failed to detect BKV in similar tumors (Arthur et al, 1994;Weggen et al, 2000;Knöll et al, 2003;Fischetti et al, 2004).…”
Section: Introductionmentioning
confidence: 97%